Transcriptome analysis of adiposity in domestic ducks by transcriptomic comparison with their wild counterparts. (June 2015) - Chen, L.; Luo, J.; Li, J. X.; Li, J. J.; Wang, D. Q.; Tian, Y.; Lu, L. Z.
Summary Excessive adiposity is a major problem in the duck industry, but its molecular mechanisms remain unknown. Genetic comparisons between domestic and wild animals have contributed to the exploration of genetic mechanisms responsible for many phenotypic traits. Significant differences in body fat mass have been detected between domestic and wild ducks. In this study, we used the Peking duck and Anas platyrhynchos as the domestic breed and wild counterpart respectively and performed a transcriptomic comparison of abdominal fat between the two breeds to comprehensively analyze the transcriptome basis of adiposity in ducks. We obtained approximately 350 million clean reads; assembled 61 250 transcripts, including 23 699 novel ones; and identified alternative 5′ splice sites, alternative 3′ splice sites, skipped exons and retained intron as the main alternative splicing events. A differential expression analysis between the two breeds showed that 753 genes exhibited differential expression. In Peking ducks, some lipid metabolism‐related genes (IGF2, FABP5, BMP7, etc.) and oncogenes (RRM2, AURKA, CYR61, etc.) were upregulated, whereas genes related to tumor suppression and immunity (TNFRSF19, TNFAIP6, IGSF21, NCF1, etc.) were downregulated, suggesting adiposity might closely associate with tumorigenesis in ducks. Furthermore, 280 576 single‐nucleotide variations were found differentiated between the two breeds, including 8641 non‐synonymous ones, and some of the non‐synonymous ones were found enriched in genes involved in lipid‐associated and immune‐associated pathways, suggesting abdominal fat of the duck undertakes both a metabolic function and immune‐related function. These datasets enlarge our genetic information of ducks and provide valuable resources for analyzing mechanisms underlying adiposity in ducks.